AKTIVITAS ANTIOKSIDAN EKSTRAK METANOL BUAH PAPRIKA HIJAU (Capsicum annum L.) - Warsi Warsi; Any Guntarti (Universitas Ahmad Dahlan, 2013)
Green paprica (Capsicum annum L.) is one of fruits which have contain–carotene, vitamin E and vitamin C, which have antioxidant activity. The aim of thisresearch is to know an antioxidant capacity of green paprica. An analysis of theantioxidant activity of this research used radical scavenging DPPH(1,1–difenil–2–pikrilhidrazil) method. The sample was preparated with maceration for4 days using methanol as the solvent. Crude extract was evaluated qualitatively using0,4 mM DPPH reagent. This result of qualitative analysis showed that green papricahave an antioxidant activity. Then, absorbance was measured using UV–Visspectrophotometer at wavelength of 517 nm. The result of this analysis obtained EC50value of green paprica was 0,3399 ± 0,01408 mg/ml.